MO337UNILATERAL NEPHRECTOMY OVERCOMES PROGRESSION TO CHRONIC KIDNEY DISEASE AFTER ACUTE INJURY IN MICE BY STIMULATING PROLIFERATION OF RENAL PROGENITOR CELLS. (29th May 2021) - Moonen, Lies; Lazzeri, Elena; Peired, Anna Julie; Conte, Carolina; D'Haese, Patrick; Romagnani, Paola; Vervaet, Benjamin
Abstract: Background and Aims: Acute kidney injury (AKI) is a global health concern with an incidence of 13.3 million patients per year, and increasing. AKI is recognized as an important risk factor for the development of chronic kidney disease (CKD). A crucial aspect for successful renal recovery after AKI is an efficient proliferative response of surviving tubular epithelial cells (TECs). Recently, we established a murine model in which the functional and histological recovery of a single kidney, injured by ischemia, is enhanced by removal of the unharmed contralateral kidney; a phenomenon termed nephrectomy-induced recovery. The renal epithelial reparative response in this unique physiological model has not been investigated, yet can provide new insights in unlocking the inherent regenerative potential of the renal epithelium. Method: AKI was induced in R26R tdTomato and PAX2/Confetti mice by left unilateral ischemia/reperfusion (UIRI) for 21 min at 34°C, after which either right nephrectomy (Nx) or no Nx was performed 3 days later. Mice were euthanized 6 weeks and 28 days after UIRI, respectively. At week 6, kidneys were weighted and renal function was assessed by serum creatinine. At 28 days, renal tissue of Pax2/Confetti mice was collected to perform renal progenitor cell lineage tracing experiments by immunofluorescence and confocal microscopy. Results: When nephrectomy was performed after UIRI, left kidney-to-body weight ratio did not change significantly over time, whereas, when no nephrectomy was performed, left kidney-to-body weight ratio gradually declined from 7, 84 ± 0, 48 mg/dl at day 3 till 3, 26 ± 0, 51 mg/dl at week 6, indicating severe atrophy in the injured left kidney. This loss of renal mass was associated with a significant increase in serum creatinine (1, 76 ± 0, 13 mg/dl) as compared to control (0, 21 ± 0, 12 mg/dl), whereas with nephrectomy, renal function fully restored. Clonal analysis in PAX2/Confetti mice revealed that nephrectomy after UIRI led to a significant increase in proliferating (i.e. clonogenic) Pax2 + progenitor cells, resulting in more multicellular clones as compared to un-nephrectomized controls. Conclusion: Nephrectomy after UIRI overcomes chronic loss of renal mass and function within the investigated 6-week time frame. This study is the first to demonstrate that nephrectomy stimulates clonal expansion of renal progenitor cells in an injured kidney, beyond that observed for spontaneous repair after UIRI. Insight in the signaling mechanisms may reveal new therapeutic approaches to incite the inherent renal regeneration potential.